Ultrasonic-time-domain-reflectometry as a real time non-destructive visualisation technique of concentration polarisation and fouling on reverse osmosis membranes - Koen, Louis Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng)--Stellenbosch University, 2000.